Intravitreal panitumumab and retinal pigment epithelium proliferation in laser-induced retinal degeneration in rabbits - Bikbov, Mukharram M.; Kazakbaeva, Gyulli M.; Panda-Jonas, Songhomitra; Valishin, Iskander D.; Nizamutdinova, Aigul M.; Jonas, Jost B. (Frontiers in ophthalmology, 2025)
This study aims to examine the effect of intravitreally applied epidermal growth factor (EGF) receptor blocker panitumumab on the proliferation of retinal pigment epithelium cells (RPE) in an experimental model of localized retinal degeneration. The experimental study included rabbits with age of 2 to 3 months and body weight of 2.5-3 kg and which were randomly distributed into a study group and control group. The right eyes received two retinal argon laser coagulation spots (500 mW; diameter, 100 μm; duration, 0.5 s), applied with an interval of 2 min at the same location close to the vascular streak in the posterior fundus region. For five times at 2-day intervals, the rabbits of the study group received intravitreal injections of 1 mg panitumumab (0.10 mL), and the rabbits of the control group had intravitreal injections of 0.10 mL Ringer's solution. At baseline, at each time point of re-examination, and at study end, the animals were examined by fundus photography and optical coherence tomography of the laser spot. The study included 19 rabbits (study group: 10 animals; control group: nine animals). After the third injection and at study end, the laser-induced area of depigmentation + hyperpigmentation combined did not vary significantly between the study group and the control group (1.43 ± 0.63 mm versus 1.63 ± 0.77 mm ; = 0.56; and 1.37 ± 0.63 mm versus 1.61 ± 0.74 mm ; = 0.46, respectively). At the same time points, the area with hyperpigmentation was significantly smaller in the study group than in the control group (0.16 ± 0.15 mm versus 0.80 ± 0.59 mm ; = 0.01; and 0.14 ± 0.14 mm versus 0.70 ± 0.56 mm ; = 0.02, respectively). At the same time points, the ratio of the hyperpigmented area to the combined depigmented + hyperpigmented area was significantly smaller in the study group than in the control group (0.11 ± 0.09 versus 0.43 ± 0.19 mm ; < 0.001; and 0.10 ± 0.08 versus 0.35 ± 0.23mm ; = 0.006, respectively). These findings indicate that intravitreally administered panitumumab was associated with reduced subretinal hyperpigmentation in a laser-induced model of retinal injury. While this may reflect a modulation of the RPE response, including the potential suppression of RPE proliferation, further studies incorporating histological and molecular analyses are warranted to confirm its effect on subretinal fibrosis.